2020
DOI: 10.1016/j.eats.2020.07.024
|View full text |Cite
|
Sign up to set email alerts
|

Open Treatment for Unstable Osteochondritis Dissecans of the Knee: Autologous Bone Grafting and Bioabsorbable Fixation

Abstract: Osteochondritis dissecans is a common osteochondral abnormality affecting the knee. In unstable lesions, the underlying bone can be significantly abnormal and necessitate treatment. Although many techniques exist, we favor an open surgical approach to ensure that the bone is properly managed. Autologous bone graft can easily be obtained locally and used to restore the bony architecture. The subsequent use of bioabsorbable implants provides a robust means of fixation that allows for single-stage surgery. This T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…The prevalence of complications related to countersunk bioabsorbable implants in the fixation of osteochondritis dissecans fragments is currently the subject of controversy in the literature. 7,17,22,27 In our study, 1 fragment was fixated with a metallic screw that necessitated planned hardware removal 6 months after index surgery. The use of biodegradeable implants eliminates this second surgical procedure, which is associated with further comorbidities and potential damage of the opposing cartilage surface.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of complications related to countersunk bioabsorbable implants in the fixation of osteochondritis dissecans fragments is currently the subject of controversy in the literature. 7,17,22,27 In our study, 1 fragment was fixated with a metallic screw that necessitated planned hardware removal 6 months after index surgery. The use of biodegradeable implants eliminates this second surgical procedure, which is associated with further comorbidities and potential damage of the opposing cartilage surface.…”
Section: Discussionmentioning
confidence: 99%
“…Fixation of unstable OCD lesions is more common in skeletally immature athletes and studies have shown return to sport rates range from 6 to 12 months in this population. 71,72 Microfracture Studies looking at the efficacy of microfracture have demonstrated successful short-term outcomes and fairly successful return to sport. 73 Concerns about the durability of the resultant fibrocartilage repair tissue have been largely proven accurate as long-term outcomes studies suggest deteriorating outcomes over time with this approach.…”
Section: Fixation Of Unstable Lesionsmentioning
confidence: 99%
“…Limited data exists regarding postoperative outcomes and return to sport for athletes who have undergone fixation of unstable osteochondral lesions. Fixation of unstable OCD lesions is more common in skeletally immature athletes and studies have shown return to sport rates range from 6 to 12 months in this population 71,72 …”
Section: Surgical Outcomes and Return To Sportmentioning
confidence: 99%
“…O steochondritis dissecans (OCD) is a pathologic condition, most commonly affecting adolescents and young adults, in which a portion of the subchondral bone detaches from its surrounding superficial structures and results in subsequent cartilage injury. 1,2 Surgical intervention is often reserved for juvenile lesions that fail conservative management, unstable lesions, detached lesions in which physeal closure will occur within 6 to 12 months, and osteochondral fragment nonunion. 1,[3][4][5] Surgical options for juvenile OCD lesions include transarticular drilling for stable lesions and fixation for unstable lesions.…”
mentioning
confidence: 99%